Anthropometric indices as predictors of obesity and metabolic risk in adolescents from Loja - Montoya Jaramillo, Verónica Luzmila (2023)
Objective: determine anthropometric indices as predictors of obesity and metabolic risk in students of the Bernardo Valdivieso–Loja Millennium Educational Unit. Methodology: Descriptive study, cross-sectional cohort, prospective, quantitative approach, population of 281 adolescents from 14 to 18 years old; by taking anthropometric measurements of height (cm) and weight (kg) to obtain BMI; the ICE by dividing the waist circumference by the height; and waist and hip circumference was calculated to obtain the WHR, determining the risk of metabolic syndrome (MS). Results: according to the BMI, they showed that 80.43% (n=226) have a normal nutritional status, with a greater tendency in women; followed by overweight 11.39% (n=11) higher in men; low weight 4.63% (n=13) predominantly in women; grade I obesity 2.49% (n=7) higher in men; grade II 0.71% (n=2) for both sexes and grade III 0.36% (n=1) higher in women; These nutritional alterations predominated in 16-year-olds, women (n=68) and men (n=49). When determining metabolic risk using ICE, 74.01% (n=208) do not present risk and 25.99% (n=73) have risk, with 13.17% (n=37) being common in women. Regarding CHD, 88.97% (n=250) have no risk, 7.12% (n=20) are at very high risk and 3.91% (n=11) are at high risk, being more common in women with 5.34% (n=15) and 3.56% (n=10) respectively. Based on the CCI, 61.57% (n=173) do not present risk and 38.43% (n=108) present risk, mostly in men 22.06% (n=62). Conclusion: the correlation is verified using Spearman's non-parametric Rho test between obesity and metabolic risk.